Non-human Agency in International Students’ Learning Realities: A Choreography of Actor-Network Theory and Rhizomes - Salomao Filho, Alfredo; Tillmanns, Tanja (Rhizome Metaphor, 2023)
This chapter explores international students’ informal learning experiences through the lenses of Deleuze & Guatarri’s rhizome philosophy and Actor-Network Theory (ANT). Reflections upon the principles of the rhizome as well as ANT ontologically symmetrical materialism are examined in light of empirical data. This analytical effort seeks to illuminate how learning is non-linearly negotiated by a series of surprising actors, coming into being as an effect of a non-essentialist set of relations. Focusing on theoretical affinity rather than divergence, the creative dialogue established between ANT and the rhizome philosophy gives space for a “choreography” of learning as a relational performance, which is enacted through international students’ practices, and objects that shift from being seemingly irrelevant to becoming matters of controversy.<br
Keywords: Postqualitative learning; Actor-network theory; Rhizome; Non-human agency; Education